2011
DOI: 10.1080/14616734.2011.554008
|View full text |Cite
|
Sign up to set email alerts
|

The establishment of an attachment research network in Latin America: Goals, accomplishments, and challenges

Abstract: In the face of a pressing need for expanded attachment research programs and attachment informed interventions in Latin America, a research network was established: Red Iberoamericana de Apego: RIA (Iberian-American Attachment Network). The purpose of RIA is to promote human development and well being, informed by attachment theory, centering on research, and with implications for public policies, education, and intervention. We report the proceedings of the second meeting of RIA held in Panama City, Panama, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…For instance, the study of the development of first-generation immigrants may be incomplete unless research is conducted to enlighten cultural and developmental dynamics prior to immigration. Likewise, the creation of research partnerships and networks could potentiate collaboration between American and international scholars (e.g., Causadias, Sroufe, & Herreros, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the study of the development of first-generation immigrants may be incomplete unless research is conducted to enlighten cultural and developmental dynamics prior to immigration. Likewise, the creation of research partnerships and networks could potentiate collaboration between American and international scholars (e.g., Causadias, Sroufe, & Herreros, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The scale was particularly designed to detect insecure attachment behaviour. Studies have reported on its use in clinical paediatric settings as part of a Chilean attachment and intervention program [ 24 ] and in the investigation of mother-infant interactions with adoptive mothers or HIV-positive women [ 25 ]. This scale is suitable from birth to 18 months, but no study has yet established its feasibility in the context of a discharge examination of a very preterm infant.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the ADS Scale has seldom been used in research, but has been widely utilized in pediatric clinical settings (Cárcamo et al., ). As part of a Chilean attachment assessment and intervention program, the ADS Scale has been used on a large scale with approximately 200,000 dyads to identify problematic attachment behaviors during regular infant checkups at 4 and 12 months (Causadias, Sroufe, & Herreros, ). Chan () utilized the ADS Scale in a study that tested the efficacy of a maternal‐sensitivity intervention with a group of adoptive and biological mothers.…”
Section: Assessment Tools Related To Attachmentmentioning
confidence: 99%